2020
DOI: 10.1016/j.heliyon.2020.e04595
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and anti-oxidative response of biologically and chemically synthesized iron oxide: Zea mays a case study

Abstract: The synthesis methodology, particle size and shape, dose optimization, and toxicity studies of nano-fertilizers are vital prior to their field application. This study investigates the comparative response of chemically synthesized and biologically synthesized iron oxide nanorods (NRs) using moringa olefera along with bulk FeCl 3 on summer maize (Zea mays). It is found that FeCl 3 salt and chemically synthesized iron oxides NRs caused growth retardation and impaired plant physiological and anti-oxidative activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Organic Se is less toxic than inorganic Se, but organic diselenides (such as selenocysteine and selenocystamine) are converted to selenols (RSeH) in the presence of thiols, which also cause production of reactive oxygen species and subsequent oxidative stress . Recently, due to the higher bioavailability and lower toxicity of Se nanoparticle (Se-NP) trace elements than inorganic salt, people’s interest in them as animal feed supplements has increased . Studies have shown that Se-NPs are less toxic to animals than other Se compounds (e.g., selenite, selenomethionine, and Se-methylselenocysteine). , Adding Se-NPs to animal feed can modulate gut microbiota and improve the growth performance, feed conversion rate, immunity, and oxidative stress ability of animals. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic Se is less toxic than inorganic Se, but organic diselenides (such as selenocysteine and selenocystamine) are converted to selenols (RSeH) in the presence of thiols, which also cause production of reactive oxygen species and subsequent oxidative stress . Recently, due to the higher bioavailability and lower toxicity of Se nanoparticle (Se-NP) trace elements than inorganic salt, people’s interest in them as animal feed supplements has increased . Studies have shown that Se-NPs are less toxic to animals than other Se compounds (e.g., selenite, selenomethionine, and Se-methylselenocysteine). , Adding Se-NPs to animal feed can modulate gut microbiota and improve the growth performance, feed conversion rate, immunity, and oxidative stress ability of animals. , …”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, due to the higher bioavailability and lower toxicity of Se nanoparticle (Se-NP) trace elements than inorganic salt, people's interest in them as animal feed supplements has increased. 10 Studies have shown that Se-NPs are less toxic to animals than other Se compounds (e.g., selenite, selenomethionine, and Se-methylselenocysteine). 11,12 Adding Se-NPs to animal feed can modulate gut microbiota and improve the growth performance, feed conversion rate, immunity, and oxidative stress ability of animals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, it has a fast growth rate which makes it easy to see the effects. There are many reports on physical and chemical methods of nanoparticles synthesis [23,24] but phytosynthesized nanoparticles and their impact on plants are rarely studied [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Hasan et al, 92 evaluated the effect of phytosynthesized FeO nanoparticles on the Zea mays crop as compared to chemically synthesized nanoparticles. The FeO nanoparticles were synthesized using aqueous extract obtained from Moringa leaves.…”
Section: Phytosynthesized Nanoparticles As Plant Growth Promotersmentioning
confidence: 99%